You substitute the y from the second eqaution to the y in the first equation
Answer:
x > -6.
Step-by-step explanation:
16x - 33x < -12x + 30
Add 12x to both sides:
16x - 33x + 12x < 30
-17x + 12x < 30
-5x < 30
x > 30/-5
x > -6
(Note the inequality signs flips because we are dividing by negative 5).
Answer:
x = 10
y = 14
Step-by-step explanation:
Here, we want to get the values of x and y
Since all sides are equal, the internal angle is 60 degrees for each internal angle
Since AC = 14
Then y is also 14 since what we have is an equilateral triangle
Secondly ;
6x = 60
x = 60/6
x = 10
23. because there is a 90 degree angle and then the 67 degree angle, and triangle law says that all angles add up to 180.
12y = 132
Now, solve for y.
Do the inverse operation.
12y = 132
12y/12 = 132/12
y= 132/12
y= 11
Equation: 12y = 132
Y equals: 11